Neoadjuvant Chemotherapy in Operable Breast Cancer: Literature Review - Costa, Mário Alberto Dantas Loures da (2013)
Introduction: Neoadjuvant chemotherapy was initially used in the systemic treatment of locally advanced and inoperable breast cancer. Based on the results obtained with this therapeutic approach, neoadjuvant treatment started to be offered to patients with operable tumors and a wide experience has already accumulated in this indication. Objectives: To conduct a review of published literature about neoadjuvant or primary chemotherapy in the treatment of breast cancer with special attention to operable breast cancer, trying to summarize the indications, treatment regimens and outcomes. Method: Data were identified through a review of articles published from 1997 to 2012, using PubMed/ Medline (www.ncbi.nlm.nih.gov/pubmed) with the words: "neoadjuvant therapy", "primary systemic therapy", "breast neoplasms" and "operable breast cancer." Results: We found in the medical literature 1,043 trials and selected 25 of them for this review (conducted prospectively, meta-analysis or cohort analysis). Conclusion: After the analysis it can be concluded that in operable breast cancer, neoadjuvant chemotherapy offers survival results equivalent to those obtained with adjuvant chemotherapy, allowing higher percentage of conservative surgery, improvement of surgical outcomes and appropriate assessment of prognosis. Treatment regimens usually employ anthracyclines, taxanes and, when indicated, biological therapy. In the experimental field, it contributes as a basis for rapid development of better and more effective treatments of breast cancer.